Effect Of Betel Quid On Gene Expression And Genetic Profiling Of Oral Squamous Cell Carcinomas - Johnson, Chong. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Oral Squamous Cell Carcinomas (OSCC) is ranked eighth most common cancer in men and recorded 274,000 cases in the year 2002 worldwide and overexpression of EpCAM, EGFR, EphB4, ESX and CKl9 genes have been reported in cancer of various origins, including OSCC. To date, little has been done to investigate the link between the cumulative effects of exposure to betel quid and variation in gene expression in normal oral mucosal cells among the local native people. In this study, these genes' expression was investigated in normal oral mucosa specimens of five chewers and two non-chewers by employing Reverse Transcription-Polymerase Chain Reaction (RT -PCR) strategy. The preliminary result suggested that betel quid does not affect these genes' expression in normal oral mucosal cells. Apart from these genes, differential gene expression of other unknown genes was studied as well using Annealing Control Primer (ACP) technology. From the result of the 20 ACP primers, all the primers produced visually comparable band intensities between the chewers and non-chewers, therefore indicating that differential gene expression was not detected between the two groups of samples using these 20 primers. Hence, the findings are unable to provide empirical prove of any relationship between effects of exposure to betel quid and variation in gene expression in normal oral mucosal cells. Apart from investigating betel quid chewing effects, the global gene expression of OSCC among the local people was investigated using cDNA microarray approach. The data on gene expression patterns revealed a total of 167 overexpressed and underexpressed genes. Among the differentially expressed genes, seven of them were validated by RT-PCR assay. These genes were TGFpI, MMPI, MMP3, MMP9, MMPIO, MMPl2 and KRT4. Most of the differentially expressed transcripts 111 I' represented novel findings while some of them are consistent with existing literature. The database provides global profile of gene expression, revealing potential role of known genes and genes that have not been previously implicated in OSCC, as well as providing information of altered genes that can be used for investigating the effects of exposure to betel quid and variation in gene expression in normal oral mucosal cells.